PTH-161 Outcome of Investigations Performed following a Positive Faecal Calprotectin: a Nine Month Pilot Study from a District General Hospital. (4th June 2013) - Rajasekhar, P T; Bevan, R; Parker, C; Rees, C; Panter, S
Abstract : Introduction: Faecal calprotectin (FCP) is a neutrophil degradation product used to detect inflammation within the gastrointestinal tract. It can aid differentiation of inflammatory bowel disease (IBD) from functional disorders and in the monitoring of IBD. We evaluated the outcome of investigations performed following a positive FCP at South Tyneside District Hospital. Methods: All positive FCP results (values > 60microg/g) were identified (1/1/12 and 30/9/12). Endoscopy and radiological results were reviewed in addition to clinic letters to understand clinician interpretation of results when necessary. Patients were categorised by age and FCP result. Outcomes in patients without IBD were categorised as: new IBD, non-specific inflammation/ulceration (NSI), peptic ulcer disease (PUD), cancer, colorectal adenoma (CRA), coeliac disease, other (including irritable bowel syndrome, bile salt malabsorption) or unknown where no additional information was available. Results: 147 positive (of 391, 37.6%) FCP results were identified. 11 were excluded, as investigations were ongoing. The outcome of investigations per category are summarised in Table 1. Conclusion: The use of FCP is increasing. In our unit, the majority are used for assessment in patients with known IBD. In patients in whom FCP was used to aid diagnosis, those with a result < 100 had a 'benign' diagnosis following investigation in both age categories suggesting a considered approach in this group may be reasonable. Disclosure of Interest: None Declared.